Mastering Selenium WebDriver 3.X test automation - Shyshkin, Dmitry (Packt, 2018)
"This course will help you learn how to create extremely reliable and stable automation tests with Selenium WebDriver. You'll learn to design advanced and easy to maintain test automation frameworks with browser factory, Page Object Models, and Selenium Grid from scratch. You'll utilize the Advanced User Interactions API to quickly spin up a Selenium Grid or run tests on the cloud. By the end of this course, you'll be able to write Selenium WebDriver tests within minutes!"--Resource description page